2013
DOI: 10.1111/myc.12078
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability inMicrosporum canisisolated from cats, dogs and humans inBrazil

Abstract: Dermatophytosis caused by Microsporum canis is a heterogeneous disease with variable clinical manifestations. M. canis is a zoophilic dermatophyte and the most frequent fungi isolated from dogs, cats and children in Brazil. The aim of this study was to investigate the genetic variability of M. canis isolates from different animal species using two microsatellite markers, namely, McGT(13) and McGT(17), and to correlate the results with the clinical and epidemiological patient data in Brazil. The study included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
19
1
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 52 publications
5
19
1
8
Order By: Relevance
“…The clinical application of these variations has to be discovered yet. These variations do not reflect differences in symptomatology or epidemiological data [14].…”
Section: A)mentioning
confidence: 69%
See 1 more Smart Citation
“…The clinical application of these variations has to be discovered yet. These variations do not reflect differences in symptomatology or epidemiological data [14].…”
Section: A)mentioning
confidence: 69%
“…Apparently, studies examining the enzyme production through molecular characterization and expression during infection are an importante means to understand the details of pathogenicity and may also answer questions related to the different degrees of virulence observed in different hosts [14][15][16][17].…”
Section: A) 3b)mentioning
confidence: 99%
“…39 Taken together, these findings indicated that MLMT is a reliable method for the differentiation of M. canis strains. 34,39…”
Section: Microsatellite Dnamentioning
confidence: 77%
“…Using two microsatellite markers, 102 strains isolated in Brazil, including 19 from human patients, yielded a total of 14 genotypes, which could be sorted into six large populations . Taken together, these findings indicated that MLMT is a reliable method for the differentiation of M. canis strains …”
Section: Intraspecies Subtyping and Strain Differentiation In Practicementioning
confidence: 87%
“…In cases of zoophilic M. canis infection, pets are a common reservoir, while in cases of anthropophilic M. audouinii and M. ferrugineum infection, the pathogens can be spread from humans. Moreover, M. canis infection is one of the most common dermatophytes, 9 and the number of anthropophilic Microsporum infections is on the rise. 10 In this study, we present two assays that enable the identification of the clinically relevant Microsporum species M. canis, M. audouinii and M. ferrugineum.…”
Section: Discussionmentioning
confidence: 99%